Enhanced dark hydrogen fermentation of Enterobacter aerogenes/HoxEFUYH with carbon cloth. (5th February 2019) - Cheng, Jun; Li, Hui; Zhang, Jiabei; Ding, Lingkan; Ye, Qing; Lin, Richen
Abstract: Long-range extracellular electron transfer through microbial nanowires is critical for efficient bacterial behaviors. The application of carbon cloth on the dark hydrogen fermentation using transgenic Enterobacter aerogenes ( E. aerogenes / HoxEFUYH ) was first proposed to enhance hydrogen production from glucose. Scanning electron microscopy images showed that the microbial nanowires between E. aerogenes / HoxEFUYH cells almost vanished due to the presence of carbon cloth. Approximately 59.1% of microorganisms concentrated in biofilms on the surface of carbon cloth, which probably promoted the intercellular electron transfer. The results from Fourier transform infrared spectra and Excitation Emission Matrix spectra indicated that carbon cloth biofilms primarily included polysaccharide and protein. Moreover, the fluorophore of biofilms (88.1%) was much higher than that of supernatant (11.9%). The analysis of soluble metabolic degradation byproducts revealed that carbon cloth selectively enhanced the acetate pathway ( C 6 H 12 O 6 + 2 H 2 O → 2 C H 3 C O O H + 2 C O 2 + 4 H 2 ), but weakened the ethanol pathway ( C 6 H 12 O 6 → 2 C 2 H 5 O H + 2 C O 2 ) . With 1.0 g/L carbon cloth, the hydrogen yield increased by 26.6% to 242 mL/g, and the corresponding peak hydrogen production rate increased by 60.3%. Highlights: H2 yield and production rate were enhanced with conductive carbon cloth. Approximately 59.1% of the microorganisms concentrated in carbon cloth biofilms. Biofilm soluble microbial products primarily included polysaccharide and protein. Carbon cloth replaced nanowires between transgenic Enterobacter aerogenes cells.